Impella-assisted transcatheter closure of an acute postinfarction ventricular septal defect. (30th March 2016) - Ibebuogu, Uzoma Nwachukwu; Bolorunduro, Oluwaseyi; Hwang, Inyong
Abstract : This case report describes a 72-year-old woman who developed an acute postmyocardial infarction ventricular septal defect (VSD) with consequent cardiogenic shock. Intra-aortic balloon pump (IABP) counter-pulsation was urgently initiated in the cardiac catheterisation laboratory, with neither clinical nor haemodynamic improvement, prompting immediate removal of the IABP and the insertion of an Impella 2.5 heart pump (AbioMed Inc; Danvers, Massachusetts, USA), a temporary ventricular assist device. Thereafter, the patient improved clinically and was admitted to the cardiovascular intensive care unit (ICU). While in the cardiovascular ICU, the patient developed worsening mechanical haemolysis of blood cells, stable but persistent cardiogenic shock and a transient ischaemic attack. A consensus decision was made to proceed with percutaneous repair of the VSD as she was deemed at high risk for surgical repair. She underwent successful percutaneous VSD repair on day 4 of hospitalisation, using a single 18 mm Amplatzer muscular VSD occluder (AGA Medical, Plymouth, Minnesota, USA) with trace residual flow across the occluder. Adequate systolic blood pressure and cardiac output was maintained postprocedure with the Impella 2.5 device. The patient, however, succumbed to multiorgan dysfunction occasioned by sepsis.